Applied behavior analysis and the zoo: Forthman and Ogden (1992) thirty years later. Issue 1 (23rd December 2022) - Fernandez, Eduardo J.; Martin, Allison L.
Abstract : The field of applied behavior analysis has been directly involved in both research and applications of behavioral principles to improve the lives of captive zoo animals. Thirty years ago, Forthman and Ogden (1992) wrote one of the first papers documenting some of these efforts. Since that time, considerable work has been done using behavioral principles and procedures to guide zoo welfare efforts. The current paper reexamines and updates Forthman and Ogden's original points, with attention to the 5 categories they detailed: (a) promotion of species‐typical behavior, (b) reintroduction and repatriation of endangered species, (c) animal handling, (d) pest control, and (e) animal performances. In addition, we outline 3 current and future directions for behavior analytic endeavors: (a) experimental analyses of behavior and the zoo, (b) applied behavior analysis and the zoo, and (c) single‐case designs and the zoo. The goal is to provide a framework that can guide future behavioral research in zoos, as well as create applications based on these empirical evaluations.